ANALISIS STRATEGI CUSTOMER RELATIONSHIP MANAGEMENT PADA PT. ALPHA CENTRAL PROPERTINDO - Hasan, Golan; Vanessa, Vanessa; Filrando, Ariendy; Christina, Christina; Reandy, Davis; Ferdawson, Ferdawson (Bussman Journal : Indonesian Journal of Business and Management, 2025)
In today’s competitive digital era, Customer Relationship Management (CRM) strategies have become a crucial element in maintaining and enhancing customer loyalty. This study aims to explore the implementation of CRM at PT. Alpha Central Propertindo, a property management company based in Batam City that actively utilizes social media and digital technology to build relationships with its customers. A qualitative-descriptive approach was employed through interviews and direct observations to understand the company’s communication strategies, service personalization, and digital innovation. The findings show that PT. Alpha Central Propertindo has successfully fostered customer loyalty through a combination of operational, analytical, and collaborative CRM strategies, as well as the use of social media as a two-way communication channel. The study also identifies several key factors contributing to CRM success, such as technological support, human resource competence, and effective program management. This research is expected to provide insights for other companies in implementing CRM effectively and sustainably.